Type 1 Cytotoxic T Cells Increase in Placenta after Intrauterine Inflammation - Liu, Jin; Liu, Yang; Panda, Snigdha; Liu, Anguo; Lei, Jun; Burd, Irina (Frontiers in Immunology, 2021)
CD8+ T cells recognize non-self antigen and kill the target through the release of proinflammatory cytokines such as interferon gamma (IFN-γ) and tumor necrosis factor alpha (TNF-𝛼). CD8+_T cell infiltration into placenta following the maternal inflammation has been associated with adverse perinatal outcomes; however, the distinct subset of CD8+ cells playing the role in perinatal sequalae are not well identified. We hypothesized that intrauterine inflammation would induce a change of properties of CD8+ T cell and its subtype Tc1/Tc2 ratio. We investigated the subsets of CD8+ T cell infiltration to placenta and their specific function in response to lipopolysaccharide (LPS) in a mouse model of intrauterine inflammation (IUI). At embryonic (E) day 17, pregnant CD-1 dams received an intrauterine injection of 25 µg LPS in100 μl PBS or 100 μl of PBS only. Flow cytometry was used to quantify CD8+ T cells, evaluate the phenotype and subtypes, and detect markers of Tc1 and Tc2 cells in placenta, at 6 hours and 24 hours post injection (hpi). Intracellular staining and flow cytometry were performed to characterize cytokines produced by CD8+ T cells. Standard statistical analysis were employed After 6 and 24 hours of LPS injection, total CD8 T cells increased (p<0.05). Tc1 cells expanded (p<0.05) in LPS-treated dams compared with the PBS group. The Tc1/Tc2 ratio was significantly higher in the LPS group than the PBS group (p<0.05). The expression of TNF-α and IFN-γ were increased in LPS group both at 6hpi and 24 hpi (p<0.05). We identified functional placental CD8+ T cell subtypes and found a significantly increase ratio of Tc1/Tc2. Following IUI, CD8+ T cells functioned primarily via production of Type 1 cytokines such as IFN-γ and TNF-α. We have provided the evidence of a Tc1-bias immune response and cytokines in mouse model of IUI.